Study of The Extent of Damage The Traditional Coconut Oil Used Repeatedly to Organoleptic Goroho Banana Chips (Musa acuminate, sp. - Mongi, Jeane J.; Mamuaja, Christine F.; Salindeho, Netty (Jurnal Ilmu dan Teknologi Pangan, 2016)
Banana chips are one of the fried snacks which preparation are very simple and have been made by most housewives, fried foods cottage level industries or even restaurantâ€™s owners. The Goroho banana chips preparation process up today still carried out using conventional frying method using poured fried oil and carried out over and over until the oil colour change. The aims of this study was to investigate the safety of used repeatedly in frying process of banana chips until the fried chips contained nutritive value as well as good taste and aroma, attractive colour and the used fried oil still have a goodÂ  quality. The Complete Randomized Design (CRD) was used as experimental design in this study with 7 kind of different fried intensity and the parameters observed on fried oil included Free Fatty Acids (FFA), Peroxide number and on the banana chips samples included organoleptic test and proximate analysis (moisture, ash, fat, crude fiber, protein an carbohydrate contents). The research results showed that lowest FFA value was observed in control treatment namely 0.16% and the highest value was found in the ninth frying treatment i.e. 0.58% and the highest peroxide number was also found in samples prepared in the twelve frying treatment namely 22.10 meq/kg. While the proximate analysis of banana chips sample showed that the samples contained moisture 3.57%, ash 1.49%, fat 39.44%, crude fiber 0.74%, protein 4.48% and carbohydrate 52.02% respectively. However the organoleptic test showed that panelists acceptability level score as like (5) until very like (6) was for the first frying intensity treatment. Keywords: frying intensity, FFA, peroxide number